U Pb and Sm Nd geochronologic studies of the eastern Borborema Province, Northeastern Brazil: initial conclusions - Van Schmus, W. R.; de Brito Neves, B. B.; Hackspacher, P. [UNESP]; Babinski, M. (Elsevier, 1995)
The Borborema Province of NE Brasil comprises the central part of a wide Pan-African-Brasiliano orogenetic belt that formed as a consequence of late Neoproterozoic convergence and collision of the São Luis-West Africa craton and the São Francisco-Congo-Kasai cratons. New Sm Nd and U Pb results from the eastern part of this province help to define the basic internal architecture and pre-collisional history of this province, with particular emphasis on delineating older cratonic terranes, their fragmentation during the Mesoproterozoic, and their assembly into West Gondwana during the Pan African-Brasiliano orogeny at ca. 600 Ma. The region can be divided into three major geotectonic domains: a) Rio Piranhas-Caldas Brandão massif, with overlying Paleoproterozoic to Neoproterozoic supracrustal rocks, north of the Patos Lineament; b) the Archean to Paleoproterozoic São Francisco craton (SFC) to the south; and c) a complex domain of Paleoproterozoic to Archean basement blocks with several intervening Mesoproterozoic to Neoproterozoic fold belts in the center (south of Patos Lineament and north of SFC). The northern and central domains comprise the Borborema Province. Archean basement gneiss and Transamazonian granulite of northern SFC are exposed in the southern part of the central domain, underlying southern parts of the Sergipano fold belt. Basement in the Rio Piranhas massif appears to consist mostly of Transamazonian (2.1 to 2.2 Ga) gneissic rocks; Nd model ages (TDM) of ca. 2.6 Ga for 2.15 Ga gneisses indicate a substantial Archean component in the protoliths to these gneisses. The Caldas Brandão massif to the east yields both Transamazonian and Archean U Pb zircon and Nd (TDM) ages, indicating a complex architecture. Metasedimentary rocks of the Jucurutu Formation yield detrital zircons with original crystallization ages as young as 1.8 Ga, indicating that these rocks may be late Paleoproterozoic and correlate with other ca. 1.8 Ga cratonic supracrustal rocks in Brazil such as the Roraima Group and Espinhaço Group. Most metavolcanic and pre-Brasiliano granitic units of the Sergipano (SDS), Pajeú-Paraíba (SPP), Riacho Pontal (SRP), and Piancó-Alto Brígida (SPAB) fold belts in the central domain formed ~ 1.0 ± 0.1 Ga, based on U Pb ages of zircons. Nd model ages (TDM) for these same rocks, as well as Brasiliano granites intruded into them and large parts of the Pernambuco-Alagoas massif, are commonly 1.3-1.7 Ga, indicating that rocks of the fold belts were not wholly derived from either older (> 2.1 Ga) or juvenile (ca. 1.0 Ga) crust, but include mixtures of both components. A simple interpretation of Brasiliano granite genesis and the Nd data implies that there is no Transamazonian or Archean basement underlying large parts of these fold belts or of the Pernambuco-Alagoas massif. An exception is a belt of syenitic Brasiliano plutons (Syenitoid Line) and host gneisses between SPAB and SPP that clearly has a Transamazonian (or older) source. In addition, there are several smaller blocks of Archean to Transamazonian gneiss that can be defined within and among these fold belts. These blocks do not appear to constitute a continuous basement complex, but appear to be isolated older crustal fragments. Our data support a model in which ca. 1.0 Ga rifting was an important tectonic and crust-forming event along the northern edge of the São Francisco craton. Our data also show that significant parts of the Borborema Province are not remobilized Transamazonian to Archean crust, but that Mesoproterozoic crust is a major feature of the Province. There are several small remnants of older crust within the area dominated by Mesoproterozoic crust, suggesting that the rifting event created several small continental fragments that were later incorporated into the Brasiliano collisional orogen. We cannot at present determine if the Rio Piranhas-Caldas Brandão massifs and the older crustal blocks of the central domain were originally part of the São Francisco craton or whether some (or all) of them came from more exotic parts of the Proterozoic Earth. Finally, our data have not yet revealed any juvenile terranes of either Transamazonian or Brasiliano age. © 1995.
Keywords: Brasiliano orogeny; collision; convergence; Gondwana; Proterozoic; samarium/neodymium dating; uranium/lead dating; Brazil, Borborema